Question
upstudy study bank question image url

3. Use the distributive property to show that the equations are equal. Examples: \( a(b+c)=a \times b+a \times c \) \[ \begin{array}{l} a\left(b^{2}+c^{2}\right)=a \times b^{2}+a \times c^{2} \\ a(b-c)=a \times b-a \times c \\ a\left(b^{2}-c^{2}\right)=a \times b^{2}-a \times c^{2} \end{array} \] a. \( \left(b^{2}+c^{3}\right) d= \) b. \( c\left(b+d^{2}\right)= \) c. \( \left(b^{2}+d^{2}\right) \times c= \) E \( \square \) d. \( d \times\left(c+b^{2}\right)= \) e. \( \left(d^{2} \times b^{3}\right)+\left(d^{2} \times c^{3}\right)= \)

Ask by Rojas Barnett. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \begin{array}{l} a. \ (b^{2}+c^{3}) d = b^{2}d + c^{3}d \\ b. \ c(b+d^{2}) = cb + cd^{2} \\ c. \ (b^{2}+d^{2}) \times c = b^{2}c + d^{2}c \\ d. \ d \times (c+b^{2}) = dc + db^{2} \\ e. \ (d^{2} \times b^{3}) + (d^{2} \times c^{3}) = d^{2}(b^{3} + c^{3}) \end{array} \]

Solution

To show that the equations are equal using the distributive property, we will apply the property step by step for each expression provided. The distributive property states that \( a(b+c) = ab + ac \). Let's go through each part: ### a. \( (b^{2}+c^{3}) d \) Using the distributive property: \[ (b^{2}+c^{3}) d = b^{2}d + c^{3}d \] ### b. \( c(b+d^{2}) \) Using the distributive property: \[ c(b+d^{2}) = cb + cd^{2} \] ### c. \( (b^{2}+d^{2}) \times c \) Using the distributive property: \[ (b^{2}+d^{2}) \times c = b^{2}c + d^{2}c \] ### d. \( d \times (c+b^{2}) \) Using the distributive property: \[ d \times (c+b^{2}) = dc + db^{2} \] ### e. \( (d^{2} \times b^{3}) + (d^{2} \times c^{3}) \) This expression can be factored using the distributive property: \[ d^{2} \times b^{3} + d^{2} \times c^{3} = d^{2}(b^{3} + c^{3}) \] ### Summary of Results 1. \( (b^{2}+c^{3}) d = b^{2}d + c^{3}d \) 2. \( c(b+d^{2}) = cb + cd^{2} \) 3. \( (b^{2}+d^{2}) \times c = b^{2}c + d^{2}c \) 4. \( d \times (c+b^{2}) = dc + db^{2} \) 5. \( (d^{2} \times b^{3}) + (d^{2} \times c^{3}) = d^{2}(b^{3} + c^{3}) \) Each expression has been simplified using the distributive property, demonstrating that they are equal to their respective expanded forms.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To demonstrate the use of the distributive property for the given scenarios: a. \( \left(b^{2}+c^{3}\right) d = b^{2}d + c^{3}d \) b. \( c\left(b+d^{2}\right) = cb + cd^{2} \) c. \( \left(b^{2}+d^{2}\right) \times c = b^{2}c + d^{2}c \) d. \( d \times\left(c+b^{2}\right) = dc + db^{2} \) e. \( \left(d^{2} \times b^{3}\right)+\left(d^{2} \times c^{3}\right) = d^{2}(b^{3} + c^{3}) \) This property allows you to factor out a common term, making it easier to manipulate complex expressions!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy